2006
DOI: 10.1021/ol060569q
|View full text |Cite
|
Sign up to set email alerts
|

[AlCl3 + 2THF]:  A New and Efficient Catalytic System for Diels−Alder Cycloaddition of α,β-Unsaturated Carbonyl Compounds under Solvent-Free Conditions

Abstract: [AlCl(3) + 2THF] is a new catalytic system for the Diels-Alder cycloaddition under SFC and air atmosphere. By using equimolar amounts of reactants, this catalyst prevents the polymerization of the diene and allows the corresponding adducts to be isolated with high regio- and stereocontrol and in excellent yields. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 21 publications
(14 reference statements)
2
18
0
Order By: Relevance
“…102 [AlCl 3 + 2THF] is a new and effiee cient catalytic system for the Diels-Alder cycloaddition of α,β-unsaturated carbonyl compounds with dienes under solvent-free conditions. 103 Dendritic copper(II) triflate catalysts with a 2,2 -bipyridine core (92) …”
Section: + 4-cycloadditionmentioning
confidence: 99%
See 1 more Smart Citation
“…102 [AlCl 3 + 2THF] is a new and effiee cient catalytic system for the Diels-Alder cycloaddition of α,β-unsaturated carbonyl compounds with dienes under solvent-free conditions. 103 Dendritic copper(II) triflate catalysts with a 2,2 -bipyridine core (92) …”
Section: + 4-cycloadditionmentioning
confidence: 99%
“…Triplet-sensitized irradiation of these bridged bicyclooctenones produced bicyclo[3.3.0]octanoids, whereas direct irradiation yielded bicyclo[4.2.0]octanes. 135 Cinchona alkaloid derivatives catalysed the enantioselective 4 + 2-cycloaddition of o-quinones with ketene enolates to produce chiral o-quinone cycloadducts in high ee ee (103) and good to excellent yields. The cycloadducts can be readily converted into optically active α-hydroxy esters in the presence of ceric ammonium nitrate.…”
Section: + 4-cycloadditionmentioning
confidence: 99%
“…[1] Our research group has been committed to the development of efficient synthetic protocols that mainly use either water as reaction medium [2] or solvent-free conditions (SolFC). [3] In particular, we have paid attention to the preparation of valuable heterocyclic moieties such as 1H-triazoles and 1H-tetrazoles, [4] dihydrodibenzo [b,d]furans, [5] biphenyl-2-carbonitrile derivatives, [6] benzo[e]1,4-oxathiepin-5-ones, [7] quinoxaliniuim, and thiazolopyridinium salts.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] We have also shown that running the reactions under solventfree conditions when a solid supported catalyst is used is a convenient approach because it allows the environmental cost to be minimized and a beneficial effect on the chemical [ …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] A few solid acid catalysts have been also found to be useful in the DA reaction. [7][8][9][10][11] In general, the heterogeneous catalysts exhibit several advantages compared with the homogeneous catalysts due to their importance in practical productions of chemicals from the viewpoints of the so-called "zeroemission" or "green" chemistry and ease of separation from the reaction mixture.…”
Section: Introductionmentioning
confidence: 99%